Validating an Innovative Guided Inquiry Learning Model for Critical Thinking in Temperature and Heat Concepts - Payu, Citron S.; Hermanto, I Made; Yunus, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This research aims to examine the validity of the development of the Guided Inquiry Learning Model based on Critical Questioning (Intersistatic) in enhancing students' critical thinking on the concept of temperature and heat. The research method used is define, design, and development. The validity of the model is evaluated through various instruments, including the content and construct validity of the learning model and the validity of instructional materials (syllabus, lesson plans, teaching materials, worksheets, and critical thinking skills tests). The research results show that the Intersistatic model obtained very valid assessments in most aspects of the evaluation. The content of the Intersistatic model received an average score of 4.29 with a percentage of 85.78%, indicating a very high level of validity. The construct assessment, with an average of 4.44 and a percentage of 88.89%, also achieved a very high level of validity. In addition, the syllabus (average 3.70, percentage 88.00%), teaching materials (average 4.61, percentage 92.22%), worksheets (average 4.26, percentage 85.19%), and critical thinking skills tests (average 4.45, percentage 89.02%) all reached a very high level of validity. The assessment of lesson plans showed good validity (average 4.24, percentage 84.73%), although it was slightly lower than other aspects. The results of this research indicate that the Guided Inquiry Learning Model based on Critical Questioning (Intersistatic) has met the criteria for good validity in various aspects of its implementation.